Urban Food Systems Governance and Poverty in African Cities - Battersby, Jane; Watson, Vanessa (Routledge Studies in Food, Society and the Environment, 2018)
This book presents the findings of an international collaborative research project that aimed to improve our understanding of the connections between urban poverty, food systems, household food security and governance, by focusing on three secondary cities in Anglophone sub-Saharan Africa.